Reframing Historical Communication for Digital-Native Youth: A Comparative Case Study of Adolescents in Yogyakarta and Global Implications for Civic Identity - Sosiawan, Edwi Arief; Suparno, Basuki Agus; Ratnawati, Ratnawati (RSF Conference Series: Business, Management and Social Sciences, 2025)
This study examines historical communication as a strategic tool for cultivating civic awareness and nationalism among digital-age adolescents, utilizing Yogyakarta, Indonesia, as a case study. Using a qualitative, comparative case study approach, data were collected from two schools, involving early to late adolescent participants, through interviews, focus group discussions, participant observation, and document analysis. The results show clear differences between developmental stages: early adolescents were more interested in emotionally charged, symbolic, and ritual-based historical narratives, while late adolescents were more interested in critical discourse that was relevant to current civic issues and digital activism. The research presents a Differential Model of Historical Communication with four interconnected dimensions: informative, inspirational, interactive, and relevant. This strategy is designed to facilitate the cognitive and emotional development of adolescents and is compatible with digital technologies. The method supports historically communicative activities that are in line with developmental paths and digital culture. Theoretically, this research amalgamates cultural memory theory, participatory communication frameworks, and adolescent developmental psychology. The concept provides age-appropriate historical teaching, digital civic education, and interactive cultural program design. The study makes a big difference in how we deal with problems in history and civic education in digital environments that are getting more complicated.